Microleakage at enamel and dentin margins with a bulk fills flowable resin - Scotti, Nicola (Medknow Publications & Media Pvt Ltd, 2014)
OBJECTIVE: The aim of this in vitro study was to evaluate the marginal sealing ability of a bulk fill flowable resin composite on both enamel and dentin substrates. MATERIALS AND METHODS: 48 non-carious molars were selected and four Class-V cavities were prepared at the CEJ of each sample. Cavities were filled with Venus Diamond (Heraeus Kulzer); Venus Diamond Flow (Heraeus Kulzer) and Surefil SDR (Dentsply). Samples were divided into two groups: First group samples were immersed in a methylene blue solution for 30 min at 25°C. Second group samples were artificially aged and then treated with methylene blue. Samples were sectioned in the center of the restoration and observed with a 40x stereomicroscope, and the percentage of cavity infiltration was calculated. RESULTS: Results were analyzed statistically by ANOVA (P < 0.05). The amount of infiltration was significantly lower for the enamel substrate compared with dentin (P = 0.0001) and in samples immediately immersed in methylene blue compared with those that were artificially aged (P = 0.011). The interaction between the composite material and the marginal substrate significantly affected dye penetration (P = 0.006). CONCLUSIONS: Bulk fill flowable resins provided significantly better marginal seal in dentin, both before and after artificial ageing. Nanohybrid resin composites and bulk fill flowable resins showed similar microleakage values at enamel margins. Bulk fills flowable resins provided significantly better marginal seal in dentin, both before and after artificial ageing. Nanohybrid resin composites and bulk fill flowable resins showed similar microleakage values at enamel margins.